2020
DOI: 10.1186/s12943-020-01157-x
|View full text |Cite
|
Sign up to set email alerts
|

The epigenetic regulators and metabolic changes in ferroptosis-associated cancer progression

Abstract: Ferroptosis, a novel form of regulated cell death, is different from other types of cell death in morphology, genetics and biochemistry. Increasing evidence indicates that ferroptosis has significant implications on cell death linked to cardiomyopathy, tumorigenesis, and cerebral hemorrhage to name a few. Here we summarize current literature on ferroptosis, including organelle dysfunction, signaling transduction pathways, metabolic reprogramming and epigenetic regulators in cancer progression. With regard to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
181
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 244 publications
(191 citation statements)
references
References 144 publications
(210 reference statements)
0
181
0
Order By: Relevance
“…Ferroptosis is a programmed cell death caused by irondependent lipid peroxidation and is different from other types of cell death, including apoptosis [14,40]. A wide variety of human diseases, including cancer, have been associated with the abnormal function of ferroptosis, and inhibition or upregulation of ferroptosis modulates the metabolic reprogramming of cancer cells [14,41]. At present, few studies have been performed on ferroptosis in KIRC, and the results also remain controversial [42].…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis is a programmed cell death caused by irondependent lipid peroxidation and is different from other types of cell death, including apoptosis [14,40]. A wide variety of human diseases, including cancer, have been associated with the abnormal function of ferroptosis, and inhibition or upregulation of ferroptosis modulates the metabolic reprogramming of cancer cells [14,41]. At present, few studies have been performed on ferroptosis in KIRC, and the results also remain controversial [42].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, sorafenib can also induce ferroptosis by triggering the expression of cathepsin B through MEK-ERK signaling phosphorylation, while inhibiting the signal transducer and activator of transcription 3 (STAT3) in human PDAC cell lines (60,62,63).…”
Section: Ferroptosis In Targeted Cancer Therapymentioning
confidence: 99%
“…Ferroptosis is recently discovered iron-dependent cell death fueled by lipid peroxidation, which differs from necrosis and apoptosis [ 322 324 ]. Mitochondrial metabolism involved series of substrates consumption, is primary source of ROS via Fenton reaction that ferrous iron mixed with hydrogen peroxide (H 2 O 2 ) is equipped with strong oxidizability to oxidize many known intracellular compounds such as carboxylic acids, alcohols and esters into inorganic states with significant oxidation effect [ 325 ]. Emerging studies has revealed ROS accumulation in a variety of cells including those within malignancies.…”
Section: Hypoxia and Targeted Therapy Via Epigenetic Interferencementioning
confidence: 99%